ASSESSMENT OF LIPID PROFILE AND ATHEROGENIC INDICES FOR CARDIOVASCULAR DISEASE RISK BASED ON DIFFERENT FISH CONSUMPTION HABITS - Devadawson, Chandravathani; Jayasinghe, Chamila; Ramiah, Sivakanesan; Kanagasingam, Arulnithy (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Habitual consumption of moderate amounts of fish is associated with reduced mortality from cardiovascular disease (CVD). However, the beneficial effects of fish-enriched diet seem contradictory due to the oxidation susceptibility of the polyunsaturated fatty acids in them. The atherogenic index is an important tool to identify people with CVD risk. Lipid profile levels are favorably affected by certain fish consumption habits, thereby decreasing the risk of coronary heart diseases. The aim of this study was to evaluate the plasma lipid profile of healthy people with different fish consumption habits and to assess CVD risk using atherogenic indices. Methods: Fasting blood samples were collected from healthy people for lipid profile estimations with an automated analyzer. Detailed information regarding physical and atherogenic parameters was collected from each participant. Results: The CVD risk profiles showed varying level with the type of fish consumption. Total cholesterol, triglyceride (TG), and non-high-density lipoprotein (Non-HDL-C) varied significantly among the types of consumers (p<0.05), whereas the high-density lipoprotein cholesterol showed variation (p<0.001). TG/HDL showed the greater level in inland fish consumers. However, atherogenic coefficient and Castelli risk index-2 did not show significant variation among type of fish eating. Atherogenic indices were borderline high riskâ€ among all fish eaters including beef eating habits. Conclusion: Fish and beef eaters had high risk among other inland and sea fish eaters. Non-HDL-cholesterol could be a marker for a serum lipid pattern associated with increased risk of heart diseases. Keywords: Cardiovascular diseases, Lipid profile, Fish consumption, Atherogenic indices.